The level of Building Information Modelling (BIM) Implementation in Malaysia - Othman, I. (Ain Shams University, 2021)
Building Information Modelling is one of the crucial topics in the construction industry. The construction industry has played an important role to assist stakeholders to successfully transfer construction practices to BIM-based technology. Currently, no systematic research that has been carried out to determine the level of BIM implementation in Malaysia. Therefore, this paper aims to evaluate the diffusion of BIM among Malaysian companies. The results of the 268 responses received revealed that only 13 of the participants from both public and private sectors are using BIM in their organization and this is a negative sign that Malaysia is still far away from the position it supposed to be in BIM implementation. Lack of awareness, costs, slow adaptation, unavailability of a clear guideline to assist organizations and policymakers toward BIM implementation transforming and that BIM was not mandated in sufficient time were observed to be responsible for the slow implementation. Â© 2020 Faculty of Engineering, Ain Shams University